THE SCHOOL MANAGEMENT FOR CREATIVE LEADERSHIP ENHANCEMENT OF STUDENT’S PROVINCIAL KINDERGARTEN SCHOOL THAILAND (CENTRAL REGION) - Usayaphan , Phanida; Sikkhabandit, Sowwanee; Punchakhetthikul, Nakamon (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed to study the school administration to enhance creative leadership in students in kindergarten schools in Thailand (Central Region). The research methodology had 3 steps: Step 1: Studying the current and desired conditions of school administration to enhance creative leadership in students using a creative leadership assessment form by teachers to assess students. The study also studied the current and desired conditions of school administration to enhance creative leadership in students. The informants included 1) one teacher responsible for student council activities from each school and 2) one student who held the position of student president from each school, totaling 44 people. Step 2: Developing a model by interviewing 5 qualified persons and experts with knowledge. Step 3: Evaluating the model from 13 informants, including school directors, deputy school directors, heads of work groups, and teachers in charge of student affairs. The research results showed that the appropriate school administration model to enhance creative leadership for kindergarten students in provincial schools in Thailand (Central Region) was an integrated model that combined the peer-based and formal administration models, allowing all personnel and education stakeholders to participate in the administration process, with an administration structure that emphasizes decentralization in a team format, and supporting workers with authority and responsibility, using reason in the decision-making process and in accordance with the agreement of the majority of personnel. It consisted of Part 1: Concepts, Principles, and Objectives; Part 2: Structure of the Administration Model and Elements; and Part 3: Implementation of the Model.